Fundamental Analysis And Technical Analysis Before Covid-19: Empirical Study On LQ45 Indexed Shares In BEI - Trisna Ayu Oktavia; Shinta Noor Anggraeny; Ahmad Kudhori (JPA : Journal of Public Accounting, 2021)
Stock investment has the potential to provide returns. Determining a portfolio is the first step for investors in investing. Commonly used stock analysis is fundamental analysis and technical analysis. The purpose of this study is to present a fundamental and technical analysis of company shares indexed by LQ45 on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The research method used is descriptive statistics. The sample of this study used a purposive sampling technique so that there were 17 companies collected. The results of fundamental analysis show that Gudang Garam Tbk, Matahari Department Store Tbk, Bukit Asam (Persero) Tbk, Surya Citra Media Tbk, and Unilever Indonesia Tbk have good ratio values. As for technical analysis, Gudang Garam Tbk Jasa Marga (Persero) Tbk Surya Citra Media Tbk Waskita Karya (Persero) Tbk shows a buy signal.